OBTAINING CITIZENSHIP IN EUROPEAN UNION MEMBER STATES THROUGH “GOLDEN VISAS”: A COMPARATIVE ANALYSIS OF THE MALTESE AND AUSTRIAN SYSTEMS (Revista Paradigma, 2025)
This article examines “Golden Visa” programs in the European Union, focusing on Malta and Austria. It explains how some countries have reduced or discontinued these investment-based pathways to citizenship, while others retain them based on sovereign decisions. The economic advantages of attracting investors are described, as well as the ethical and social risks involved. In addition, it compares each country’s requirements and procedures, underlining the diversity of approaches within the EU’s policy environment and realities.